Quality of Life, Satisfaction, Occlusal Force, and Halitosis after Direct and Indirect Relining of Inferior Complete Dentures - Sônego, Mariana Vilela; Neto, Clóvis Lamartinede Moraes Melo; dos Santos, Daniela Micheline; Moreno, André Luiz de Melo; Bertoz, André Pinheiro de Magalhães; Goiato, Marcelo Coelho (European Journal of Dentistry, 2021)
Objective The aim of this study was to compare the direct relining technique with the indirect relining technique in relation to quality of life, satisfaction with the relining, occlusal force, and halitosis of users of acrylic complete dentures.Materials and Methods Twenty bimaxillary edentulous individuals were selected. They had to use the same pair of complete dentures for a minimum of 1 year and a maximum of 5 years. The subjects were randomly divided in groups of direct relining and indirect relining of the inferior denture (n = 10). Both groups received the same silicone-based relining. The clinical tests verified the quality of life (Oral Health Impact Profile in edentulous individuals), the satisfaction with the relining, the occlusal force, and halitosis. The tests (halitosis and occlusal force) were performed initially (before the relining), immediately after the relining, and 30, 60, 90, and 180 days after the relining. The questionnaires (quality of life and satisfaction with the relining) were performed initially (before the relining), and 30, 60, 90, and 180 days after the relining.Statistical Analysis Analysis of variance and the Tukey test were used (p < 0.05).Results There was no statistical difference comparing the two techniques in all the evaluations (p < 0.05). There was a significant statistical difference for the factor of time in all clinical tests for each relining technique (p < 0.05). The quality of life and satisfaction with the relining increased significantly 30 days after the relining when compared with the initial time point, for both techniques (p < 0.05). The occlusal force increased significantly after 90 and 180 days when compared with the initial time point, for both techniques (p < 0.05). Halitosis decreased significantly immediately after the relining when compared with the initial time point, for both techniques (p < 0.05).Conclusion Independent of the relining technique used, there was an increase in the quality of life, satisfaction with the relining, and occlusal force, as well as a reduction in the level of halitosis. Both techniques generated similar results and therefore can be options in clinical practice.
Keywords: denture relining; complete denture; quality of life; bite force; dental prosthesis; edentulous mouth; edentulous jaws